Social security disability law and the American labor market - Dubin, Jon C. (New York : New York University Press, 2021)
Passing down nearly a million decisions each year, more judges handle disability cases for the Social Security Administration than federal civil and criminal cases combined. Jon C. Dubin challenges the contemporary policies for determining disability benefits and work assessment. He posits the fundamental questions: where are the jobs for persons with significant medical and vocational challenges? And how does the administration misfire in its standards and processes for answering that question? Deploying his profound understanding of the social security administration and disability law and policy, he demystifies the system, showing us its complex inner mechanisms and flaws, its history and evolution, and how changes in the labor market have rendered some agency processes obsolete.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Disability insurance -- Law and legislation -- United States; Social security -- Law and legislation -- United States; Labor market -- United States; Labor laws and legislation -- United States; Law; Social welfare & social services; Laws of specific jurisdictions & specific areas of law; Employment & labour law: general; Disability & the law